2010
DOI: 10.3233/jad-2010-091249
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Coffee as Therapeutics Against Alzheimer's Disease

Abstract: Abstract. Epidemiologic studies have increasingly suggested that caffeine/coffee could be an effective therapeutic against Alzheimer's disease (AD). We have utilized a transgenic mouse model for AD in well-controlled studies to determine if caffeine and/or coffee have beneficial actions to protect against or reverse AD-like cognitive impairment and AD pathology. AD mice given caffeine in their drinking water from young adulthood into older age showed protection against memory impairment and lower brain levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(89 citation statements)
references
References 29 publications
4
80
1
4
Order By: Relevance
“…We chose not to use decaffeinated coffee for these studies because it contains 60 % less chlorogenic acids and 70 % less chlorogenic acid lactones than caffeinated coffee (Chu et al 2009). In addition, in contrast to the results seen with caffeine and caffeinated coffee, decaffeinated coffee was previously unable to decrease plasma amyloid-beta when provided to AD mice (Arendash and Cao 2010).…”
Section: Introductioncontrasting
confidence: 67%
See 2 more Smart Citations
“…We chose not to use decaffeinated coffee for these studies because it contains 60 % less chlorogenic acids and 70 % less chlorogenic acid lactones than caffeinated coffee (Chu et al 2009). In addition, in contrast to the results seen with caffeine and caffeinated coffee, decaffeinated coffee was previously unable to decrease plasma amyloid-beta when provided to AD mice (Arendash and Cao 2010).…”
Section: Introductioncontrasting
confidence: 67%
“…Furthermore, the overall contribution of individual components of coffee to the health benefits of coffee consumption has not been explored. In a series of studies using AD transgenic mice, Arendash and colleagues found that caffeine can protect against, and even reverse, memory loss and AD pathology (Arendash and Cao 2010). In addition, caffeine and/or caffeinated coffee (but not decaffeinated coffee) affected plasma levels of amyloid-beta in mice and humans with AD (Arendash et al 2006;Cao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mouse models of Alzheimer's and Parkinson's diseases found that caffeine could alleviate pathological signs and behavior deficits in these neurodegenerative disease paradigms, by antagonizing A2A adenosine receptors (Arendash and Cao, 2010;Prediger, 2010;reviewed in Cunha and Agostinho, 2010). Moreover, administration of caffeine and other stimulants in orexin/ataxin-3 transgenic narcoleptic mice induced an increase in motor activity but the effects on neuropathology remain to be investigated (Okuro et al, 2010) and should be further investigated in MJD models.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…These drugs have included acetylcholine precursors, muscarinic agonists, nicotinic agonists, andacetylcholinesterase inhibitors [9] . Herbal drugs are alsopre-clinically as well as clinically tested and shown to be very effective as Galantamine [19,20] , Ginkgo biloba [21,22] , Bacopa monnieri (brahmi) [23,24] , Celastrus paniculatus [25,26] , Curcumin [27][28][29] , coffee [30][31][32] and Lavender essential oil [33] . Many naturally occurring compounds have been proposed as potential therapies to slow or prevent the progression of AD, mostly by acting as antioxidants [34] , but also with some direct anti-amyloid actions [35] .…”
Section: Polyphenol Ellagic Acid-targeting To Brain: a Hidden Treasurementioning
confidence: 99%